CULTURE-SPECIFIC VOCABULARY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Culture is a broad concept that includes the specific characteristics, customs, traditions and values of humanity, which forms its own vocabulary in each society. Culture-specific vocabulary develops mainly within the historical, social and cultural context of that society. A culture-specific dictionary is a dictionary containing words, phrases, terms and their meanings specific to a particular culture, nation or society. This dictionary contains special terminology related to the customs, traditions, historical experiences and social life of that culture. Each culture has its own words and expressions. is expressed. For example, terms related to traditional foods, customs, or holidays. Culture-specific vocabulary reflects the historical and cultural context of that culture. These words often represent the historical experiences, values and worldview of that people. Culture-specific vocabulary plays an important role in strengthening social ties. It facilitates communication between people and strengthens bonds through traditions. Every culture contains its own values and beliefs. These values are reflected in the vocabulary and determine the moral and aesthetic standards of society. Culture-specific vocabulary is important in preserving cultural heritage that is passed down from generation to generation. It allows new generations to learn and understand their culture. Cultural vocabulary is an important tool that reflects the identity, history and cultural heritage of a nation or society. It helps people to understand, appreciate and preserve their culture.